2022
DOI: 10.3389/fped.2022.900606
|View full text |Cite
|
Sign up to set email alerts
|

Uncovering incontinentia pigmenti: From DNA sequence to pathophysiology

Abstract: Incontinentia pigmenti (IP) is an X-linked dominant genodermatosis. The disease is known to be caused by recurrent deletion of exons 4–10 of the Inhibitor Of Nuclear Factor Kappa B Kinase Regulatory Subunit Gamma (IKBKG) gene located at the Xq28 chromosomal region, which encodes for NEMO/IKKgamma, a regulatory protein involved in the nuclear factor kappa B (NF-κB) signaling pathway. NF-κB plays a prominent role in the modulation of cellular proliferation, apoptosis, and inflammation. IKBKG mutation that result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 70 publications
0
12
0
Order By: Relevance
“…Mutations in the IKBKG (formerly known as NEMO/IKKγ ) gene located at Xq28 have been found to cause the disease expression [ 4 , 6 ]. The most common genetic mutation in IP is an approximately 11.7-kb deletion in the IKBKG gene that removes exons 4 through 10.…”
Section: Discussionmentioning
confidence: 99%
“…Mutations in the IKBKG (formerly known as NEMO/IKKγ ) gene located at Xq28 have been found to cause the disease expression [ 4 , 6 ]. The most common genetic mutation in IP is an approximately 11.7-kb deletion in the IKBKG gene that removes exons 4 through 10.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, studies on genotype-phenotype correlations are very rare and suggest that variant type, affected domain, status of XCI and genomic background may all contribute to the high phenotypic variability reported in IP patients ranging from mild skin alterations to severe central nervous system (CNS) abnormalities 7 . Interestingly, loss-of-function variants have been shown to coincide a higher likelihood of skewed or extremely skewed XCI 26 and skewing seems to negatively correlate with disease severity and CNS involvement 27 .…”
Section: Discussionmentioning
confidence: 99%
“…The former is surprising, since hyperpigmented areas of the skin develop in as much as 98% of affected females and can persist up to the fourth decade of life 25 , while hypopigmented skin areas have been suggested to be dramatically underreported in the past 24 . Furthermore, studies on genotype-phenotype correlations are very rare and suggest that variant type, affected domain, status of XCI and genomic background may all contribute to the high phenotypic variability reported in IP patients ranging from mild skin alterations to severe central nervous system (CNS) abnormalities 7 . Interestingly, loss-of-function variants have been shown to coincide a higher likelihood of skewed or extremely skewed XCI 26 and skewing seems to negatively correlate with disease severity and CNS involvement 27 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous reports have shown that incontinentia pigmenti (IP; OMIM 308300) is a very rare genetic disease with skin lesions as a typical feature, accompanied by multisystem developmental disorders, and can involve teeth, eyes, the central nervous system and other organs. 1 , 2 The incidence of this disease is 1.2 per 100,000 births. Because male patients often die in the uterus, the incidence of pigment incontinence is concentrated in female patients.…”
Section: Introductionmentioning
confidence: 99%